Faktor Penyebab Ketidaklengkapan Pengisian Rekam Medis Pasien Rawat Inap Di Rumah Sakit - Selvia Juwita Swari; Maria Verawati (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2022)
The completeness of medical records with 100% standard plays a role in improving health services in hospitals. The purpose of this study was to analyze the factors causing the incomplete filling of inpatient medical records at the hospital using 5M management elements, namely man, money, method, material, and machine, with literature study research methods. The literature selection was based on inclusion and exclusion criteria from databases such as Google Scholar, Crossref, Jember State Polytechnic e-Library, and Portal Garuda. The literature used is 16 articles. The result obtained are the man element due to indiscipline, high workload, inappropriate educational background, knowledge of the benefits, usefulness and impact of incompleteness, training, age, tenure of officers, element of money due to limited budgets, the method element is due to the implementation not being in accordance with the SOP, no reward and punishment system, less effective monitoring and evaluation, monitoring and evaluation have not been carried out, material elements due to less systematic form arrangement, and machine elements due to inadequate facilities and infrastructure. To solve the problem, providing training, preparing exclusively budgets, conduct socialization of SOP, improve form design structure, monitoring and evaluating SOP’s, impose reward and punishment, complete the facilities and infrastructure.